KOMPETENSI MENGAJAR GURU EKONOMI SMA KABUPATEN PURWOREJO - S. Eko Putro Widoyoko (Jurnal Cakrawala Pendidikan, 2005)
AbstractThis research aims to reveal : (1) the teaching competencies level of High School Economics teachers in Purworejo regency, (2) the contributionof the educational background, the teaching experience and the working spirit toward the teaching competencies of High School Economic teachers in Purworejo regency.This research was an ex-post facto study which the subjects of all High School Economic teachers at Purworejo regency. The sample of this research was 40 teachers, which determined based on Krejcie formula, and the proportional random sampling technique. The data collecting instrument was a Likert scale question, each of which had been tested by factor analysis, Alpha Cronbach and split-half Spearman-Brown technique for fulfilled the requirements of validity and reability. The data analysis used a descriptive and inferential analysis.The result of the descriptive analysis showes that the teaching competenciesof High School Economic teachers in Purworejo regency are 17,5% in high category; 65,0% in sufficient category; 17,5% in poor category. The result of the partial correlation analysis shows : (1) the educational background is not provides a significant contribution to the teaching competencies of High School Economic teachers in Purworejo regency, (2) the teaching experience provides a positive and significant contribution i.e 17,58% to the teaching competencies of High School Economic teachers in Purworejo regency, (3) the working spirit providesa positive and significant contribution i.e 26,2% to the teaching competencies of High School Economic teachers in Purworejo regency. The result of multiple regression analysis indicates that there are a positive and significant contribution of the teaching experience and the working spirit i.e 41,6% simultanneously to the teaching competenciesof High School Economic teachers in Purworejo regency. Thus, it can be concluded that in general the teaching competencies of High School Social Studies teachers in Purworejo regency is in sufficient category. There is a significant contribution of the teaching experience and the working spirit both individually and simultaneously toward the teaching competencies of High School Economic teachers in Purworejoregency.Key words: teaching competencies, educational background, teaching experience, working spirit